Development and validation of new RP-HPLC method for the determination of Amlodipine in tablet dosage form manufactured by IIUM pilot plant - Helal Uddin, A.B.M.; Alaama, Mohammed; Mohamad, Huda Jamilah; Amiruddin, Noor Syafawati (2013)

(untitled)
Background: Amlodipine is a third generation dihydropyridine calcium antagonist, It is used in the treatment of hypertension and angina. It is formulated in IIUM pilot plant in the tablet dosage form, an analytical method is needed for the analysis of amlodipine to qualify the GMP requirements. The pharmacopeia method was tested and found to be very old and non-economic as it caused the column to spoil earlier. Objective: To develop and validate new sensitive and cheap analytical method for the analysis of amlodipine in tablet dosage form. Methodology: Standards and samples were prepared by dissolving amlodipine or amlodipine tablets in mobile phase and sonicate for 5 min. Samples were analysed using Agilent 1200 Series RP-HPLC equipped with quaternary pump and auto injector. Samples were injected to C18 column and the mobile phase consisted of ammonium acetate buffer (pH=4 adjusted using glacial acetic acid) and acetonitrile in the ratio 60-40. The flow rate was 1 ml/min and UV detector was used for the detection and the wavelength was 248nm.The method was validated according to ICH guidelines. Results: The retention time was 3.4 min with the total run time of 6 min. The method was linear over the range 0.1-40 ug/ml with R2 = 0.999. The recovery was 98%, and the method showed high precision and repeatability. All validated parameters were in the accepted range of ICH requirements. Conclusion: New rapid sensitive and highly economic method was developed and validated for the analysis of amlodipine in tablet dosage form.